Efficacy of Structured Teaching Programs in Improving Oral Hygiene Knowledge among School Children at Alkharj, Saudi Arabia - Inderjit M. Gowdar; Zaid A. Alogily; Abdullah I. Alenazi; Mahfouz A. Basuliman; Muaadh H. Alamodi; Abdulaziz F. Alsubaie (Wolters Kluwer Medknow Publications, 2024)
Introduction: Children's knowledge of oral hygiene is very important to have a good oral health. Health education intervention is the best way to impart oral hygiene knowledge to children, which is cost-effective also. Aim of the Study: To evaluate the effectiveness of a structured teaching program in improving the existing oral hygiene knowledge of children in the age group of 10-12 years. Methodology: A randomized control trial was planned with one intervention group and control group. A pre-intervention test was conducted in both the groups to assess baseline oral hygiene knowledge among children. After the pre-test, the intervention group children were educated through a structured teaching program for a period of 2 weeks. Again, post-test was conducted in both the groups after a gap of a week. Results: The pre-intervention oral hygiene knowledge scores were 8.43 ± 3.93 in the intervention group and 8.44 ± 3.90 in the control group. Post intervention, the oral hygiene knowledge score was 15.34 ± 2.37 in the intervention group and 8.96 ± 1.37 in the control group. A 45.04% increase in knowledge was observed in the intervention group. The results were statistically highly significant (P < 0.05). Conclusion: A structured teaching program is an effective way to impart knowledge among school children; furthermore, long-term follow-up studies are needed to evaluate oral hygiene knowledge gained through the program.